The Analisis Talent Acquisition dan Job Satisfaction Terhadap Employee Perfomance pada Karyawan CV. Roda Mas - Padila Nurmala; Umban Adi Jaya (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to analyze the influence of Talent Acquisition and Job Satisfaction on Employee Performance of CV. Roda Mas Auto Lestari employees. The pre-survey showed low effectiveness of career development, job satisfaction, and a high Turn Over Rate of 40.60%. This quantitative study involved 93 employees as the population and sample with a saturated sampling technique. Data were collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression through SPSS. The results show that partially Talent Acquisition has no positive and significant effect on performance, while Job Satisfaction has a positive and significant effect. Simultaneously, both have a positive and significant effect. This indicates that good Talent Acquisition is not enough to improve performance without the support of internal factors such as job satisfaction. Based on the Resource-Based View (RBV) theory, this study emphasizes HR as a strategic asset and suggests optimizing the company's Talent Acquisition system.